The Effect of Village Public Service Quality on Community Life and Public Trust: Evidence from Sukamerindu Village - Hedyan Putra; Nurul Jannah (Journal of Citizenship, 2026)
Village-level public services constitute a critical interface between the state and citizens and play a pivotal role in shaping the quality of local governance and community trust. This study examines the implications of public service delivery for social life and public trust in Sukamerindu Village by analyzing service quality, structural constraints, and the use of information technology in village administration. Employing a quantitative explanatory design, data were collected through a structured questionnaire administered to 114 residents who had directly accessed village public services. The data were analyzed using descriptive statistics and simple linear regression with the support of SPSS. The findings indicate that the overall quality of public services is perceived as high, particularly in terms of officials’ attitudes, clarity of administrative requirements, and procedural simplicity. Nevertheless, respondents also reported moderate to high structural constraints, including unclear service workflows, limited administrative staffing, and inadequate facilities. The utilization of information technology has contributed to faster and more efficient administrative processes; however, its effects remain uneven due to disparities in digital access and digital literacy among residents. Regression analysis demonstrates that public service quality has a statistically significant influence on community life and public trust, accounting for 46.5% of the observed variance. These findings underscore that village public services extend beyond administrative functions and constitute a key determinant of social experience and institutional trust at the local level. Keywords: Public Service Quality; Village Governance; Public Trust; Rural Community